Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1128/jcm.43.2.942-944.2005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Etest MBL for Detection of bla IMP-1 and bla VIM-2 Allele-Positive Clinical Isolates of Pseudomonas spp. and Acinetobacter spp

Abstract: The Etest MBL (AB BIODISK, Solna, Sweden) correctly differentiated all 57 isolates of Acinetobacter spp. and Pseudomonas aeruginosa with the bla IMP-1 allele and 135 of 137 (98.5%) Acinetobacter spp. and Pseudomonas spp. isolates with the bla VIM-2 allele. The Etest MBL was reliable for detecting the IMP-1-and VIM-2-producing Pseudomonas and Acinetobacter isolates.The IMP-and VIM-type and other acquired class B metallo-␤-lactamase (MBL)-producing gram-negative bacilli have been increasingly isolated from clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
1
9

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 17 publications
1
24
1
9
Order By: Relevance
“…Our results were in accordance with those obtained by Berges et al but not with those obtained by Picão et al (2,15). Most previous studies evaluating MBL phenotypic detection were performed under distinct experimental conditions, jeopardizing comparison of their results (6,11,14). The sizes of inhi- bition zones produced by ␤-lactam-IMBL combinations may differ according to the way that IMBL is incorporated into the ␤-lactam disks (1).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results were in accordance with those obtained by Berges et al but not with those obtained by Picão et al (2,15). Most previous studies evaluating MBL phenotypic detection were performed under distinct experimental conditions, jeopardizing comparison of their results (6,11,14). The sizes of inhi- bition zones produced by ␤-lactam-IMBL combinations may differ according to the way that IMBL is incorporated into the ␤-lactam disks (1).…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, we added the IMBL solutions directly on ␤-lactam disks already placed on the agar plate, as described by Picão et al, whereas some authors first prepare and freeze IMBL-␤-lactam disks; thus, the results of our CD assay may be comparable to those of studies using the same methodology (1,15,25). It has been suggested that the selection of the optimal MBL screening method be based not only on bacterial species but also on the strains collected and the local prevalence of MBL producers (11,15).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…isolates (11,14,17,21,25); (v) a lack of results stratified according to pathogen/species, in which the SN and SP values reflect the overall performance of all isolates (2,14,17); and (vi) accurate statistical analysis usually is not carried out to interpret and validate their results (2,11,21,37,38). This is the first study to assess the accuracy of phenotypic methods to detect all of the major types of mobile MBLs described (GIM, IMP, SIM, SPM, and VIM) that are produced by diverse bacterial genera with distinct imipenem susceptibility patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Although they are simple to perform and cheaper than genotypic methods, they have shown discordant results depending on the employed methodology, ␤-lactam substrates, MBL inhibitors (IMBL), and bacterial genus tested (11,14,17,21,26). In addition, SPM-, GIM-, and SIM-producing pathogens rarely have been evaluated by these studies.…”
mentioning
confidence: 99%